Synergistic Antioxidant and Anti-Inflammatory Effects of Phenolic Acid-Conjugated Glutamine-Histidine-Glycine-Valine (QHGV) Peptides Derived from Oysters (Crassostrea talienwhanensis) - Soyun Choi; Sohee Han; Seungmi Lee; Jongmin Kim; Jinho Kim; Dong-Ku Kang (MDPI AG, 2024)
The glutamine-histidine-glycine-valine (QHGV), a peptide derived from oysters, exhibits antioxidant activity and is being actively researched as a potential pharmaceutical and functional cosmetic ingredient. In this study, we synthesized the QHGV peptide and explored the hitherto unknown anti-inflammatory effects of QHGV. The antioxidant property was also characterized by conjugating with various naturally derived phenolic acids, such as caffeic, gallic, ferulic, sinapinic, and vanillic acids. Conjugation with phenolic acids not only enhanced the antioxidant activity of QHGV but also diminished the lipopolysaccharide-induced generation of reactive oxygen species (ROS) in the murine macrophage cell line, RAW 264.7. The reduction in the levels of reactive oxygen species led to the reduced mRNA expression of inducible nitric oxide synthase (iNos) and cyclooxygenase 2 (Cox-2), resulting in an anti-inflammatory effect through the inhibition of the phosphorylation of mitogen-activated protein kinase, including extracellular signal-activated protein kinase, c-Jun NH2-terminal kinase, and p38. Furthermore, the phenolic acid-conjugated peptides increased the mRNA and protein levels of collagen type I, indicative of a wrinkle-improvement effect. The phenolic acid conjugates of the peptide were not cytotoxic to human keratinocytes such as HaCaT cells. These results suggest that phenolic acid conjugation can enhance the potential of peptides as drug and cosmetic resources.